Cornell H. Mayer papers - Mayer, Cornell H., 1921-2005.
Correspondence, writings, scientific notebooks, topical files, biographical material, printed matter, scrapbooks, photographs, and other papers documenting Mayer's career with the Naval Reseach Laboratory (U.S.) during which he improved radio telescope technology and measured the surface temperatures of Venus and other planets. Documents Mayer's participation in expeditions to observe solar eclipses from the Aleutian Islands, Alaska, and from Sweden.
Electrical engineer and radio astronomer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Naval Research Laboratory (U.S.); Planets -- Atmospheres; Radio astronomy; Radio telescopes; Scientific expeditions -- Alaska -- Aleutian Islands; Scientific expeditions -- Sweden; Solar eclipses; Venus (Planet) -- Atomsphere; Astronomers; Engineers